Plasma Ceramides, Mediterranean Diet, and Incident Cardiovascular Disease in the PREDIMED Trial (Prevención con Dieta Mediterránea) - Wang, Dong D.; Toledo, Estefanía; Hruby, Adela; Rosner, Bernard A.; Willett, Walter C.; Sun, Qi; Razquin, Cristina; Zheng, Yan; Ruiz-Canela, Miguel; Guasch-Ferré, Marta; Corella, Dolores; Gómez-Gracia, Enrique; et al. (Circulation (New York, N.Y.), 2017)
Although in vitro studies and investigations in animal models and small clinical populations have suggested that ceramides may represent an intermediate link between overnutrition and certain pathological mechanisms underlying cardiovascular disease (CVD), no prospective studies have investigated the association between plasma ceramides and risk of CVD. The study population consisted of 980 participants from the PREDIMED trial (Prevención con Dieta Mediterránea), including 230 incident cases of CVD and 787 randomly selected participants at baseline (including 37 overlapping cases) followed for ≤7.4 years. Participants were randomized to a Mediterranean diet supplemented with extra virgin olive oil, a Mediterranean diet supplemented with nuts, or a control diet. Plasma ceramide concentrations were measured on a liquid chromatography tandem mass spectrometry metabolomics platform. The primary outcome was a composite of nonfatal acute myocardial infarction, nonfatal stroke, or cardiovascular death. Hazard ratios were estimated with weighted Cox regression models using Barlow weights to account for the case-cohort design. The multivariable hazard ratios (HR) and 95% confidence intervals (CIs) comparing the extreme quartiles of plasma concentrations of C16:0, C22:0, C24:0, and C24:1 ceramides were 2.39 (1.49-3.83, <0.001), 1.91 (1.21-3.01, =0.003), 1.97 (1.21-3.20, =0.004), and 1.73 (1.09-2.74, =0.011), respectively. The ceramide score, calculated as a weighted sum of concentrations of four ceramides, was associated with a 2.18-fold higher risk of CVD across extreme quartiles (HR, 2.18; 95% CI, 1.36-3.49; <0.001). The association between baseline ceramide score and incident CVD varied significantly by treatment groups ( =0.010). Participants with a higher ceramide score and assigned to either of the 2 active intervention arms of the trial showed similar CVD risk to those with a lower ceramide score, whereas participants with a higher ceramide score and assigned to the control arm presented significantly higher CVD risk. Changes in ceramide concentration were not significantly different between Mediterranean diet and control groups during the first year of follow-up. Our study documented a novel positive association between baseline plasma ceramide concentrations and incident CVD. In addition, a Mediterranean dietary intervention may mitigate potential deleterious effects of elevated plasma ceramide concentrations on CVD. URL: http://www.isrctn.com. Unique identifier: ISRCTN35739639.